PURIFICATION OF NATURAL GAS FROM HYDROGEN SULFIDE BY SORBENTS BASED ON ZEOLITE (Scientific journal of the Fergana State University, 2024)
By processing local raw materials Navbakhor bentonite with the salts of calcium, zinc and magnesium, zeolite with a composition of / was prepared in laboratory conditions. The sorption capabilities of zeolites prepared from local raw materials were studied and a technological scheme was developed by adding metal salts to the sorbent and subsequent heat treatment. A / catalyst based on zeolite sorbents has been developed for drying oil and natural gas from water vapor and removing sulfur compounds, their texture and sorption properties have been studied. During X-ray diffraction analysis of the surface of the / catalyst, the total amount of the ionic phase Ca2+, Zn2+ and Mg2+ was studied. At JSC "UZBEKGAZ" - Mubarek gas processing plant, experimental tests were carried out to study the sorption properties of this catalyst, with the comparative sorption of sulfides with the participation of /. The sorption properties of HSZ catalysts have been studied. Experimental tests of the CaA(5A) catalyst were carried out for comparison, which showed hydrogen sulfide absorption equal to 8.2% by weight, and our developed catalyst / with a total capacity of 14.3% by weight.